Virtual Reality in Marketing: A Framework, Review, and Research Agenda - Alcañiz, Mariano; Bigné, Enrique; Guixeres, Jaime (Frontiers in Psychology, 2019)
Marketing scholars and practitioners are showing increasing interest in Extended Reality technologies (XRs) such as virtual reality (VR), augmented reality (AR) and Mixed Reality (MR), as very promising technological tools for producing satisfactory consumer experiences that mirror those experienced in physical stores. However, most of the studies published to date lack a certain measure of methodological rigor in the characterization of the XR technologies and in the assessment techniques used for characterizing the consumer experience, which limits the generalization of the results. We claim that it is necessary to define a rigorous methodological framework for the use of XR in marketing. This article reviews the literature on the use of XR in marketing, and provides a conceptual framework for organizing this disparate body of work.